Exploring the HIV/AIDS infection, intimate partner violence experience and poor mental health syndemic and its association with parenting amongst women in Mpumalanga - Silima, Mpho (University of the Witwatersrand, Johannesburg, 2024)
Background: In South Africa, women disproportionately bear the burden of Intimate Partner Violence (IPV), HIV or AIDS, and poor mental health (MH), which significantly affects their parenting and children’s wellbeing. Harsh and inconsistent parenting, often resulting from these compounded stressors, negatively impacts the health and development of children. While there is extensive research on the impact of each epidemic on parenting, there is considerably less published research on the syndemic impact of IPV, HIV, and MH. A syndemic refers to the synergistic interaction of two or more co-existing epidemics where the combined impact is often greater than the sum of their individual effects, often leading to more severe health outcomes, particularly among vulnerable or marginalised populations. Aim: The overall aim of this PhD research was to explore the experiences and parenting practices among mothers and caregivers living with different combinations of the co-occurring IPV, MH, and HIV epidemics. Methods: This thesis draws upon three distinct studies, using an overall mixed-method study design. The first is a scoping review of 23 studies conducted between 2001-September 2023, following the JBI and Prisma-ScR guidelines. The second study is a nested qualitative study using in-depth interviews and arts-based methods with 20 women. Thematic data analysis using MAXQDA22 was used to analyse the data. The third study is a secondary data analysis of cross- sectional data of young adults who are primary caregivers of children under 18 from the third wave of a multigenerational longitudinal study. A total of 720 young women completed an interviewer administered questionnaire, and 547 were included in the final quantitative analysis. Quantitative data were analysed using Stata 17.0 using logistic regression and marginal effects models Results: This doctoral research contributes several new findings to the extant literature on parenting practices and the IPV, MH, and HIV syndemic. The scoping review identified primarily studies from the United States, that utilized quantitative, mainly longitudinal research designs. Findings from the review indicate living with the different combinations of IPV, MH and HIV led to increased likelihood of harsh and inconsistent parenting. Furthermore, the review viii revealed that while IPV was not directly associated with harsh parenting practices, the relationship was mediated by poor mental health. Anxiety and maternal depression were the most frequent disorders found in studies examining the co-occurrence of HIV-MH. Findings from the qualitative studies revealed that women living with the syndemic face numerous challenges due to these co-existing epidemics, with depression, suicidality, and post-traumatic stress disorder (PTSD) being most common. Participants adopted various coping strategies, including religion, acceptance, and family support, with harmful substance use most prevalent among those experiencing IPV. Regarding parenting, individual, interpersonal, and structural factors significantly influenced practices. The quantitative findings revealed that maternal (includes any woman who is a primary caregiver) use of emotional and physical violence was common, with women experiencing IPV and poor MH concurrently, having higher odds of using both physical and emotional violence towards their children, particularly emotional violence. The quantitative findings also revealed a synergistic relationship between IPV and MH, showing that the combined effect of these epidemics has a more severe impact on parenting than each independently However, combinations including HIV, such as HIV-MH and IPV-MH did not significantly increase the risk of maternal use of emotional violence Conclusion: This research highlights the severe effects of the IPV, MH syndemics on parenting among South African women. Multi-sectoral and multi-disciplinary interventions are needed to address the challenges experienced by mothers and caregivers living with the syndemic. To effectively reduce child maltreatment, interventions must tackle the IPV-MH syndemic in tandem. The overlap of these epidemics leads to detrimental parenting, strained relationships and inadequate provision of children’s needs. Additionally, mothers living with these syndemics often have lower levels of parenting satisfaction, which further compounds their challenges. Addressing these intersecting epidemics holistically is essential for improving the wellbeing of both parents and their childre
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Intimate partner violence; Mental Health; HIV/AID; SDG-3: Good health and well-being